Design and analysis of DC-to-14-GHz and 22-GHz CMOS cascode. - Ren-Chieh Liu (IEEE Journal of solid state circuits)
The designs of two fully integrated CMOS cascode distributed amplifiers (DAs) with 14-GHz and 22-GHz bandwidth are presented. Cascode gain cells and m-derived matching sections are used to enhance the gain and bandwidth performance. These amplifiers demonstrated the highest frequency and widest bandwidth of operation for amplifiers using regular CMOS processes to date. This paper also describes the analysis to design the cascode CMOS DA, together with the small-signal models, EM simulation of the spiral inductors on the silicon substrate, and the analysis of the cascode device. Good agreement between measured and simulated results was achieved for both of the DA designs.